2021
DOI: 10.1111/ijpo.12873
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and prospective associations of sleep duration and bedtimes with adiposity and obesity risk in 15 810 youth from 11 international cohorts

Abstract: Summary Objectives To investigate associations of bedtimes and sleep durations with adiposity levels in children and adolescents. Methods Individual data were pooled for 12 247 children (5819 with follow‐up adiposity at 2.3 ± 1.4 years post‐baseline) and 3563 adolescents from 11 international studies. Associations between questionnaire‐based sleep durations, bedtimes and four groups of combined bedtimes and sleep lengths (later‐shorter [reference]/earlier‐shorter/later‐longer/earlier‐longer) with measured adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Correspondingly, a prospective analysis of accelometer-measured data demonstrated that an optimal sleep on-set for adiposity outcomes for about 11-year-old children would be between 21:00 and 22:00, but the effect remained dependent on sleep duration (Collings et al, 2022). Based on our and others' findings, we speculate that inconsistency in bedtimes and sleeping occurs most likely due to screen time and socialising with peers.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Correspondingly, a prospective analysis of accelometer-measured data demonstrated that an optimal sleep on-set for adiposity outcomes for about 11-year-old children would be between 21:00 and 22:00, but the effect remained dependent on sleep duration (Collings et al, 2022). Based on our and others' findings, we speculate that inconsistency in bedtimes and sleeping occurs most likely due to screen time and socialising with peers.…”
Section: Discussionsupporting
confidence: 60%
“…Positive associations were seen in two studies using self-reported bedtime (Asarnow et al, 2015;Quach et al, 2016), while no association was shown in a study using an objective measure of sleep-onset among 823 8-year-old children in New Zealand (Taylor et al, 2020). Besides these, we found two other longitudinal studies with 16,000 and 5819 participants (Collings et al, 2022;Swindell et al, 2021). Late self-reported bedtime during week contributed to higher body fat percentage in a 10 year follow-T A B L E 2 Cross-sectional associations of bedtime and delay in bedtime on school and non-school nights with BMIz and WtHr with three models (n = 10,245) using linear regression up of initially 9-11-year-old children from United Kingdom, and the effect was independent of known covariates (Swindell et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although several studies have linked sleep to body composition in children and adolescents, these associations are primarily based on the relationship between short and long sleep durations and BMI and adiposity [ 13 ]. However, the causality of this relationship is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Walch et al (2016) examined sleep at a broad level and found that a country's average bedtime predicted the people's total sleep duration, whereas wake time did not predict sleep duration. Late bedtimes have also been associated with physical and mental health risks (Morrissey et al, 2020), including obesity (Collings et al, 2021; Olds et al, 2011), and increased risks of having anxiety, mood, and behavioral disorders, as well as substance use and even suicidality (Zhang et al, 2017). Disruptions in bedtime (and SOT) and wake time can also impact other areas of health and functioning, as seen in the challenges that arise with starting back to school after having late or inconsistent sleep schedules in the summer or on weekends (Crowley & Carskadon, 2010), or even adjusting to daylight saving changes (Rishi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%